Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-3 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Human spinal cord with dorsal (A) and ventral side (B,C). Intumescentia cervicalis and lumbosacralis are visible. The caudal ventral roots are thinner than the dorsal roots. The passage of the artery spinalis magna (Artery of Adamkiewicz) and the anterior spinal artery are indicated. The C5 and Th10 roots and the intercostal nerve Th12 are indicated. Dissection of the Author.